Comparison of urinary KIM-1 and NGAL and plasma creatinine in patients undergoing coronary artery bypass graft surgery - Maryam Saeedi Ghaheh; Saeed Mardani; Afsaneh Malekpour; Farzaneh Kadkhodaei Elyaderani; Fatemeh Salehi Choliche; Nayereh Mortazavi; Shadi Botshekan (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: Serum creatinine level is currently being used as an indicator to detect acute kidney injury (AKI) after cardiac surgery, which is delayed and unreliable. Objectives: This study was conducted to determine the AKI in patients undergoing coronary artery bypass graft (CABG) surgery by measurement of urinary creatinine and plasma kidney injury molecule (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL). Patients and Methods: In this cross-sectional study, 96 patients undergoing CABG were divided based on their serum creatinine level of the fourth day after procedure into two groups of AKI (an increase of creatinine more than 0.3 mg/dl or more than 150 % of its baseline level) and non-AKI. In both groups urinary KIM-1 and urinary NGAL were measured on the first day of surgery (first 24 h). Results: No significant difference was observed in baseline creatinine between the two groups (P>0.05). However postoperative serum creatinine, creatinine changes, urinary NGAL and KIM1 showed significant difference between the groups (P<0.05). Serum creatinine was positively correlated with KIM-1 (r = 0.666, P<0.001) and NGAL (r = 0.660, P<0.001). KIM-1 and NGAL had high ability to detect AKI [area under the ROC (receiver operating characteristic) curve of 0.929 and 0.838, respectively]. The NGAL at cut-off point of 97.4 had 86% sensitivity and 80% specificity and KIM-1 at cut-off point of 14.8 had 84% sensitivity and 89% specificity. Conclusion: KIM-1 and NGAL had high ability to detect AKI. However, KIM-1 had higher detection ability than that of NGAL.